The Effect of Village Funds, Family Hope Program (PKH), Population, and Joint Business Groups (KUBE) on Poverty in Kurun District Gunung Mas Regency - Albert Easton; Alexandra Hukom; Benius Benius (DINASTI RESEARCH, 2025)
This study analyzes the influence of Village Funds, the Family Hope Program, Joint Business Groups, and population growth on poverty reduction in Kurun District, Gunung Mas Regency, Central Kalimantan. Poverty remains a major development challenge despite the implementation of several government programs designed to enhance rural welfare. The research aims to identify the effectiveness of fiscal transfers and empowerment initiatives in improving economic independence and reducing poverty levels. The study employs a quantitative approach with panel data regression to assess secondary data from 13 villages during 2018–2024. The Common Effect Model was selected as the best estimation model based on specification tests. The findings reveal that Village Funds, the Family Hope Program, and Joint Business Groups have a significant negative effect on poverty, demonstrating their roles in enhancing income, infrastructure development, and community empowerment. In contrast, population growth has a significant positive impact, indicating that demographic expansion increases poverty levels when not accompanied by economic growth. The results underscore the importance of integrated policy coordination between fiscal, social, and demographic strategies to achieve sustainable poverty reduction and equitable rural development in Indonesia.